RETRACTED: KEARIFAN BUDAYA LOKAL; Sebagai Benteng Munculnya Konfik Agama - Muhammad Alfan Sidik (Madania: Jurnal Ilmu-Ilmu Keislaman, 2017)
RETRACTION TO:Daulay, N., & Hikmah, H. (2020). Pengaruh Motivasi dan Lingkungan Kerja Terhadap Kinerja Karyawan PT Poetra Jaya Sukses Mandiri Di Kota Batam. Jurnal Kajian Manajemen Bisnis, 9(1) (doi: https://doi.org/10.24036/jkmb.10806000This article has been retracted by Publisher based on the following reason:The Editor of MADANIA: Jurnal-Jurnal Keislaman  found the double publication in the article publishing due to article's content similarity published in https://journal.walisongo.ac.id/index.php/JSW/article/view/2035Sidik, M. A. (2017). Kearifan Budaya Lokal sebagai Benteng Munculnya Konflik Agama. JSW (Jurnal Sosiologi Walisongo), 1(2), 161-176.One of the conditions of submission of paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process